Between "Degeneration" and "Revival": Female Images in the ‘New Objectivity’ Painting - Koroleva, Anastasia Yu. (Actual Problems of Theory and History of Art, 2022)
Female images in art are one of the eternal themes, which more-less belong to all styles and art directions. Such themes are a kind of a channel of social communication, a mirror of consciousness of the epoch. The works demonstrating the changing of women’s status are of special interest.  The beginning of 20th century in German culture, was a period of Weimar republic (1919–1933), when the social settings were strongly rethought.The art of New Objectivity balanced between two extreme dots — “degeneration” and “revival”, between ugliness und classicism. In one time, it is represented by two nearly opposite lines — “verists” and “magic realists” (“neoklassicists” or “quasiklassicists”).The art of New Objectivity with its specific “neorealism” of artistic means firstly represents the social phenomenon with its significant critical tendency. This is the feature that distinguishes it from other earlier avant-garde divisions, such as Fauvism, Cubism, and even Expressionism with its subjectivism and reflection. The main aim of the study is to review female images in German art of the 1920s — beginning of the 1930s revealing a specific creative method and following features of artistic mind, which is very important for understanding the essence of German art of the abovementioned period.It shows us very different foreshortenings of German society of that time, from grotesque sharp images of O. Dix, G. Gross, R. Schlichter, and K. Hubbuch, to bourgeois polite images of A. Kanoldt, G. Schrimpf, K. Mense, and idealized by K. Schad.
Keywords: New Objectivity; art of Weimar republic; verism; magic realism; female images; female portrait; social criticism